PARENTING EDUCATION; MEWUJUDKAN BDR YANG AKTIF DAN MENYENANGKAN BAGI ANAK - Khulusiniyah Khulusiniyah; Farhatin Masruroh (LP2M Universitas Ibrahimy, 2021)
Parenting education activities are carried out with the theme of realizing an active and fun study from home, as a mentoring activity for teachers and parents of children. Complaints of parents when accompanying their children to study at home, became the main basis for carrying out these parenting activities. Many parents feel overwhelmed to build children's enthusiasm in learning and completing the tasks given by the teacher. This condition bring out the initiative to provide assistance to teachers in providing parenting education activity material to children's parents and also directly provide material about the study from home method in parenting education activities carried out at RA Al Hidayah Kapongan Situbondo, so that even though learning activities were carried out at home , the children are still enthusiastic to do it actively and fun. The most important thing in this mentoring activity is to bring back the essence of parents/mothers as madrasas for their children, so that parents can hone, love, and nurture their children well. In the end, a nation will be born as khaira ummah who is anfauhum linnas.